Frequency of Temporomandibular Disorders in Asymptomatic Removable Partial and Complete Denture Wearers - N. Dulčić; V. Jerolimov; J. Pandurić (Applied Bionics and Biomechanics)
A dogmatic view on occlusion as the main aetiological factor for temporomandibular disorder (TMD) has been present in the literature for a long time, but a direct scientific correlation between occlusal disorders and TMD has never been proven. The purpose of this study was to determine the frequency of TMD signs and tissue-specific diagnoses in a population of 164 asymptomatic participants, 70 removable partial denture wearers and 94 complete denture wearers of an average age of 61.3 years, by means of clinical manual functional analysis. TMD was found in 42.1% of the participants. No statistically significant difference in the occurrence of TMD was found between removable partial and complete denture wearers and between genders (P > 0.05). The most frequent tissue-specific diagnoses were osteoarthrosis (11%), total anterior disc displacement (9.1%) and partial anterolateral disc displacement (8.5%). The frequency of tissue-specific diagnoses was also not influenced by the type of prosthetic replacements.